Minimally Invasive Esophagectomy in Semi-Prone Position (Pawar Technique): Technical Aspects and Outcome in 224 Patients - Pawar, Suraj B.; Bagul, Kiran G.; Anap, Yogesh S.; Tanawade, Prasad K.; Mane, Ashwini; Patil, Snehdeep S.; Pawar, Reshma S.; Kulkarni, Shubham S.; Pawar, Aditya S. (South Asian Journal of Cancer, 2020)
Background and Objectives There are two patient positions described for minimally invasive esophagectomy (MIE) for esophageal cancer, viz., left lateral and prone positions. To retain the benefits and overcome the disadvantages of these positions, a semi-prone position was developed by us. Our objective was to analyze the feasibility of performing MIE in this position.Materials and Methods A retrospective review of patients who underwent MIE at our center from January 2007 to December 2017 was done. A semi-prone position is a left lateral position with an anterior inclination of 45 degrees. Intraoperative parameters including conversion rate, immediate postoperative outcomes, and long-term oncological outcomes were analyzed.Statistical Analysis Statistical Package for the Social Sciences version 19 (IBM SPSS, IBM Corp., Armonk, New York, United States) was utilized for analysis. Survival analysis was done using Kaplan-Meier graph. Quantitative data were described as mean or median with standard deviation, and qualitative data were described as frequency distribution tables.Results Consecutive 224 patients with good performance status were included. After excluding those who required conversion (14 [6.6%]), 210 patients were further analyzed. Median age was 60 years (range: 27–80 years). Neoadjuvant treatment recipients were 160 (76%) patients. Most common presentation was squamous cell carcinoma (146 [70%]) of lower third esophagus (140 [67%]) of stage III (126 [60%]). Median blood loss for thoracoscopic dissection and for total operation was 101.5 mL (range: 30–180 mL) and 286 mL (range: 93–480 mL), respectively. Median operative time for thoracoscopic dissection alone was 67 minutes (range: 34–98 minutes) and for entire procedure was 215 minutes (range: 162–268 minutes). There was no intraoperative mortality. Median 16 lymph nodes were dissected (range: 5–32). Postoperative complication rate and mortality was 50% and 3.3%, respectively. Disease-free interval was 18 months (range: 3–108 months) and overall survival was 22 months (range: 6–108 months).Conclusion MIE with mediastinal lymphadenectomy in a semi-prone position is feasible, convenient, oncologically safe, which can combine the benefits of the two conventional approaches. Further prospective and comparative studies are required to support our findings.
Keywords: thoracoscopic surgery; minimally invasive surgery; esophagectomy; patient positioning